2022
DOI: 10.18280/ts.390422
|View full text |Cite
|
Sign up to set email alerts
|

Classification of OME with Eardrum Otoendoscopic Images Using Hybrid-Based Deep Models, NCA, and Gaussian Method

Abstract: Otitis media with effusion (OME) is defined as a middle ear disease that occurs with the accumulation of fluid in the posterior part of the eardrum, usually without any symptoms. When OME disease is not treated, some negative consequences arise that deeply affect the education, social and cultural life of the patient. OME disease is a difficult issue to diagnose by specialists. In this article, autoendoscopic images of the eardrum have been classified using deep learning methods to help specialists in the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Harun Bingol [ 59 ] proposed a hybrid-based deep learning model for classifying Otitis Media with Effusion (OME) based on eardrum otoendoscopic images. The proposed model combined Neighborhood Component Analysis (NCA) and the Gaussian method to extract and select features.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Harun Bingol [ 59 ] proposed a hybrid-based deep learning model for classifying Otitis Media with Effusion (OME) based on eardrum otoendoscopic images. The proposed model combined Neighborhood Component Analysis (NCA) and the Gaussian method to extract and select features.…”
Section: Related Workmentioning
confidence: 99%
“…Experimental results on a dataset comprising 910 images indicated that the proposed model achieved a high accuracy of 94.8%. Harun Bingol [ 59 ] presented a novel approach for classifying cervical cancer on Gauss-enhanced Pap-smear images using a hybrid CNN model. The performance of the proposed model was tested on a dataset comprising 1000 images, and it was found to achieve an accuracy of 93.6%, which is better than that of various other existing methods.…”
Section: Related Workmentioning
confidence: 99%
“…There exist several issues that arise in farming because of several environmental aspects and this disease in plant leaves is termed to be a strong aspect that causes deficiency in the quality of agricultural products. The aim is to alleviate this problem with machine learning (ML) models ( Bayram, Bingol & Alatas, 2022 ; Bingöl, 2022a , 2022b ). Several ML and segmentation models are devised for the categorization and discovery of diseases in plants through leaf images ( Subramanian et al, 2022 ; Krishnamoorthy et al, 2021 ; Sathishkumar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important advantages are that it allows the early diagnosis of the disease, increasing the chance of treatment of the patient, as well as getting rid of the treatment costs, which are highly likely to occur in the advanced stages of the disease. Deep architectures have been frequently used in the biomedical field, especially in recent years 3–6 . In addition, another important advantage is to provide pre‐diagnosis to sick people in underdeveloped regions where there are no specialists or the number of specialists is insufficient, thanks to these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Deep architectures have been frequently used in the biomedical field, especially in recent years. [3][4][5][6] In addition, another important advantage is to provide pre-diagnosis to sick people in underdeveloped regions where there are no specialists or the number of specialists is insufficient, thanks to these technologies.…”
Section: Introductionmentioning
confidence: 99%